ENTERIC FEVER: IN ERA OF ANTIBIOTIC RESISTANCE. A RETROSPECTIVE STUDY - Amanullah Lail; Bakhtiar Ahmed Bhanbhro; Asif Ali Khuhro; Pardeep Kumar; Iftkhar Haider; Sonia Saleem (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Salmonella typhi and Salmonella paratyphi are the common causes of enteric fever, agastrointestinal infection that is characterized by systemic clinical signs. The oral-fecal pathway isthe main means of transmission, and humans are the only known reservoir for this bacteria. Within14 daysofinfection,clinicalsignsusually showup asfever, vomiting, diarrhea, andabdominalpain. Due to its high rates of morbidity and mortality, enteric fever isa major global health concern.Children are more proneto this ailment,especially in thesummerand during therainy season.Objective:To examineantibioticresistancein entericfeverin children.Studydesign:Ananalyticalcross-sectionalstudyPlace and Duration:This study was conducted in Pir Abdul Qadir Shah Jilani Institute of MedicalSciencesGambatfrom September 2022 to September2023.Methodology: childrenwith enteric fever symptoms were selected at random from a hospital with awell-functioning laboratory. Two blood samples were drawn from different locations and submittedforsensitivityandculturetesting.OurstudycomprisedchildrenwhoseSalmonellatyphiorparatyphi isolates were positive. Considering the patients' ages, we separated them into three groups.Patients in the first group were under 2to 5 years of age; those in the second group were between 6 to 10years old; and thosein thethirdgroup were11 to 15years of age.Results: A total of 200 childrenwere included in this research. Overall 136 participants were male, while 64were female. Considering the patients' ages, weseparated them into three groups. Patients in thefirst group were under 2to 5 years of age (n = 42), those in the second group were between 6 to 10 yearsold(n=108),andthoseinthethirdgroup wereabove11 to 15yearsofage(n=50).Theagerangewith the highest levels of antibiotic resistance was 6 to 10years old. Furthermore, resistance rateswerenoticeablygreaterinthosewhohadtakenantibioticsbeforeseekingmedicalassistance.Antibioticresistancewasmorecommon in male patientsthan in femalepatients.Conclusion: Patients between the ages of 6 to 10years showed a considerably higher level ofresistancethan patients under theageof2 to 5 years or patients over the ageof 11 to 15years.